Understanding the impact of hydrodynamics on coastal erosion in Latin America: a systematic review - Vallarino Castillo, Ruby; Negro Valdecantos, Vicente; del Campo, José María (Frontiers in Environmental Science, 2023)
Coastal zones in Latin America support a significant regional population and are vital for providing essential ecosystem services that underpin crucial socio economic activities. However, these zones face pressing challenges, with coastal erosion being a prominent concern. Coastal erosion not only jeopardizes coastal stability but also leads to occasional loss of natural habitats. This is particularly worrisome for sandy beaches due to the consistent shoreline retreat in specific regions. Short term adverse effects of coastal erosion are often attributed to human activities. Nonetheless, the influence of hydrodynamic processes, intensified by extreme events, is gaining prominence. This is due to the combined impact of tides, waves, currents, and other factors, resulting in accelerated shoreline retreat and significant losses of infrastructure and beach areas across Latin America. This article conducts a comprehensive analysis of case studies in Latin America related to coastal erosion due to hydrodynamic processes. Employing a systematic review approach, data is extracted from Scopus and Web of Science databases. From an initial dataset of 701 records, 62 records meet strict eligibility criteria. Case studies present evidence of how hydrodynamic processes interact with various factors, encompassing oceanic climatic conditions, atmospheric climatic conditions, anthropogenic influences, geomorphological and bathymetric characteristics, geological and tectonic factors, and climate change related aspects. These interactions have an immediate and significant impact on sandy beaches, emphasizing the necessity of comprehensively addressing these linkages when analyzing shoreline changes. This approach aids in identifying key erosion mechanisms and developing effective mitigation measures. Furthermore, the article provides a concise overview of data sources, tools, and methodologies identified in the case studies, spanning from field investigations to the utilization of geographic information systems and numerical models. Underscores the crucial role of international academic collaboration in coastal erosion research, facilitating the adoption of innovative methodologies from other regions, potentially offering a more comprehensive perspective in the formulation of mitigation and adaptation strategies. Finally, potential areas for future research in Latin America are explored, including the assessment of extreme event variability and its impacts on local and regional hydrodynamic processes. This aspect holds critical importance in steering future research towards scenarios that encompass economic and social considerations.